Efficacy of Itraconazole Versus Terbinafine for the Treatment of Tineacruris. - Shakya, Nabin Bhakta; Jha, Sagar Mani; Dangol, Anil; Shakya, Sanil; Shah, Aparna (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Tenia Cruris is the commonest dermatophyte infection which is common in men and aggravated by warm humid condition Teniarubrum is the main species for the disease1, 2. Itraconazole and Terbinafine are the better newer drugs for the therapeutic option due to their efficacy, convenient and less side effect. Itraconazole is a wider spectrum Thiazole group of fungistatic drugs which inhibit sterol 14 ? demethylase impairing biosynthesis of fungal ergosterol. Similarly Terbinafine is broad specturmallylamine group of fungicidal activity which inhibits squalene 2, 3 epoxidase enzyme thus inhibit fungal biosynsthesis of ergosterol3-5. These two drugs have been needed conventionally as a pulse and continuous therapy. The main aim of this study is to compare the efficacy of both drugs and to recommend the eff ective treatment in case of Teniacruris. Methods: In this randomized comparative study, the efficacy and safety of oral itraconazole (n=35) and terbinafine (n=35), each given for 2weeks, was compared in patients with tineacruris within the period of 1 year study. Results: The final evaluation at week 4 showed a cure rate of 91.4% for itraconazole and 82.9% for terbinafine. No definite adverse effect was noted. Conclusions: Itraconazolehas high cure rate and less failure rate without side effects in comparision to Terbinafine. Medical Journal of Shree Birendra Hospital; Jan-June 2012/vol.11/Issue1/24-26 DOI: http://dx.doi.org/10.3126/mjsbh.v11i1.7763